Effects of Reactor Loading and Solvent Addition on Catalyst-Free Glycerolysis of Palm Oil - Ittirit Phichaion; Ruengwit Sawangkaew; Winatta Sakdasri; Somkiat Ngamprasertsith (My University, 2021)
Glycerol is a by-product of biodiesel production.Every three moles of biodiesel produced, glycerol is released in one mole, which is around 10 wt.% of the total products.The crude glycerol from supercritical transesterification has a higher purity than that from alkaline transesterification.Monoglyceride is an anionic surfactant widely used in many applications.In this work, the glycerolysis reaction of palm oil and glycerol was studied using isopropanol as the solvent.The investigated important parameters in this study were reaction time in range of 30-150 minutes, reactor loading in range of 40-80 %, and molar ratio of isopropanol to glycerol to palm oil in range of 0-30.The glycerol to palm oil molar ratio was constant at 5 to 1.The results showed that parameters affected conversions and yields were reactor loading and solvent addition.The highest monoglyceride yield, 37.4%, was obtained at 260 ˚C in 150 minutes and 40 % of reactor loading.Molar ratio of glycerol to palm oil to isopropanol is 5:1:15.A central composite design (CCD) of 48 experiments investigated the effects on monoglyceride content (%MG) of temperature (220 to 260 ˚C), reaction duration (30 to 150 min), and molar ratio of IPA to palm oil (0:1 to 30:1).The %MG was substantially and statistically significantly enhanced (p < 0.0001) at higher temperatures and longer reaction duration.An analysis of variance confirmed that the molar ratio of IPA to palm oil had a much less significant effect (p = 0.0255) on %MG.The crude glycerol obtained from a biodiesel production plant was compared with pure glycerol at the optimal condition.A %MG of 46.58% was observed using crude glycerol as reactant because of the yield-limiting effects of water in crude glycerol.
Keywords: Food Chemistry and Fat Analysis